Comparative Study of Intercultural Awareness Between Indonesia and Ghana in ELT - Arifin, Nurul; Friatin, Lilies Youlia; Sugiarto, Bambang Ruby (JALL (Journal of Applied Linguistics and Literacy), 2024)
The globalization of education and increasingly multicultural nature of the classroom, English teachers must develop intercultural awareness and competence. However, comparative studies that specifically focus on the experiences of foreign English teachers are limited. Thus, the research aims to investigate and compare the similarities and differences of the intercultural awareness and practices of Indonesian and Ghanaian English teachers in the context of English language teaching. As well as the strategies of teaching materials and techniques they employ to promote intercultural understanding among their students. This research used qualitative methods within the framework of a comparative study design and data were collected through semi-structured interviews. The participants were 2 EFL teachers from Ghana and Indonesia. The researcher analyzed it to identify patterns by organizing, coding and summarizing the data into themes. The study's findings indicated the critical importance of integrating intercultural awareness in English teaching, emphasizing the recognition and value of cultural diversity. This motivates teachers to foster an inclusive, tolerant environment using culturally appropriate teaching materials and techniques, ensuring all students feel valued. The Ghanaian teacher in international schools promotes global cultural acceptance or called as intercultural awareness, blending diverse cultures into lessons, while the Indonesian teacher prioritizes local culture or basic cultural awareness in English teaching. However, this research has limitations on the application of integration, teaching materials and techniques in intercultural awareness in English language teaching. So that future research can explore these aspects more broadly and varied.